Analisis Penerapan Pembelajaran Berbasis Kontekstual (Contextual Teaching and Learning) pada Mata Pelajaran Bahasa Arab - Triani Triani; Sudarmadi Putra (Nusantara: Jurnal Pendidikan Indonesia, 2023)
This study aims to describe and analyze Contextual Teaching and Learning (CTL) in Arabic subjects at SMPIT Al-Falaah Simo. This type of research is descriptive with a qualitative approach. The source of information for this research is the head of SMPIT Al-Falaah Simo, Arabic teachers, and students. Data collection techniques are carried out through observation, interviews and documentation. The findings in this study include that: 1. The application of CTL in Arabic subjects at SMPIT Al-Falaah Simo goes through three stages; the preparation stage, the implementation stage, and the evaluation stage. In this application, it has contained seven components of CTL such as constructivism, questioning, inquiry, learning community, modeling, reflection, and authentic assessmen. 2. There are several obstacles in the application of CTL in Arabic subjects at SMPIT Al-Falaah Simo; Teachers have not mastered and understood contextual learning methods comprehensively, limited learning resources, limited time in the context of mentoring students, the situation of teaching and learning activities that teachers create is not always the same from day to day, and limited facilities such as the absence of a language laboratory.